2022
DOI: 10.3389/fpsyg.2021.773227
|View full text |Cite
|
Sign up to set email alerts
|

The Psychological and Biological Impact of “In-Person” vs. “Virtual” Choir Singing in Children and Adolescents: A Pilot Study Before and After the Acute Phase of the COVID-19 Outbreak in Austria

Abstract: Psychobiological responses to music have been examined previously in various naturalistic settings in adults. Choir singing seems to be associated with positive psychobiological outcomes in adults. However, evidence on the effectiveness of singing in children and adolescents is sparse. The COVID-19 outbreak is significantly affecting society now and in the future, including how individuals engage with music. The COVID-19 pandemic is occurring at a time when virtual participation in musical experiences such as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 80 publications
0
7
0
Order By: Relevance
“…In-person sessions were also associated with significant decreases in levels of salivary cortisol, whereas virtual sessions were associated with increases. The cortisol decreases for in-person sessions was mirrored by a decrease in self-reported stress levels, and an increase in self-reported calmness (Grebosz-Haring et al, 2021). This finding suggests that even though remote music therapy can be beneficial, in-person sessions may lead to enhanced efficacy.…”
Section: / 14mentioning
confidence: 75%
See 1 more Smart Citation
“…In-person sessions were also associated with significant decreases in levels of salivary cortisol, whereas virtual sessions were associated with increases. The cortisol decreases for in-person sessions was mirrored by a decrease in self-reported stress levels, and an increase in self-reported calmness (Grebosz-Haring et al, 2021). This finding suggests that even though remote music therapy can be beneficial, in-person sessions may lead to enhanced efficacy.…”
Section: / 14mentioning
confidence: 75%
“…This helped to provide patients with an additional avenue of support when they later transitioned out of the hospital environment. However, direct comparisons between in-person and virtual singing sessions for children indicate that there are greater benefits from in-person sessions (Grebosz-Haring, Schuchter-Wiegand, Feneberg, et al, 2021). A very small study that was conducted before and during the pandemic indicated that both in-person and…”
Section: / 14mentioning
confidence: 99%
“…There is currently a lack of evidence to support whether participants in health-focused choirs receive the same or similar benefits in online choir settings compared to in-person group singing. Preliminary research by Grebosz-Haring et al (2022) found that for school-aged children and adolescents, benefits of singing on mood were present in both face-to-face singing pre-COVID-19 and during online choir singing in 2020, but that psychobiological effects (on outcomes such as salivary cortisol, psychological stability, self-contingency and quality of life) were markedly greater for the in-person setting. A qualitative study by Thompson et al (2023) found that participants of a therapeutic choir for people living with dementia and care-partners experienced positive psychological benefits during online singing, however, the qualitative nature of this study and the fact that it was completed during the height of pandemic lockdowns make it difficult to draw conclusions about the ongoing benefits of online choir participation.…”
Section: Discussionmentioning
confidence: 99%
“…(p. 13) Guided by this view, we planned to undertake a systematic review of controlled studies of creative arts activities/arts therapy for children and young people experiencing mental health problems based on earlier pilot studies in Salzburg. [4][5][6] However, our preparatory work revealed some concerns. The first regarded the quality of the published research on the effects of arts programs and therapy for young people with mental health challenges, and the second was a lack of critical evaluation in recent reviews of this literature.…”
Section: Suggest Thatmentioning
confidence: 95%